BACTERIOLOGICAL AND CLINICAL PROFILE OF COMMUNITY ACQUIRED PNEUMONIA IN HOSPITALIZED PATIENTS - VINAY DHARMADHIKARI; TINKU JOSEPH; AJIT KULKARNI (International Journal of Pharma and Bio Sciences, 2013)
The aim of our study was to determine the bacteriological and clinical profile of community acquired pneumonia patients requiring hospital admission. CAP was defined as per BTS guidelines. 65/104 cases of study group turned out to be culture positive for definitive bacterial etiology. The Commonest cause for CAP was Streptococcus pneumoniae (19/65) followed by, Klebsiella pneumoniae (17/65), Staphylococcus aureus (13/65), Pseudomonas aeruginosa (8/65), Escherichia coli (4/65), Acinetobactor spp. (3/65). Smoking (52%) and chronic alcoholism (28%) were major risk factors and COPD (23%) and Diabetes mellitus (19%) were major co-morbidities associated with CAP in the study group. The mortality was 8% cases after therapy and Pseudomonas aeruginosa was commonest cause of it. Death occurred exclusively in elderly people, all of whom were suffering from co- morbidities and had an initial CURB-65 a score of three. Limitation of our study was the inability to isolate atypical micro organisms. This emphasizes the need for further studies.